IMPLEMENTATION OF IP-TECHNOLOGIES IN THE AERONAUTICAL TELECOMMUNICATION NETWORK OF UKRAINE - Konakhovych, Heorhii; Kozliuk, Iryna; Doroshenko, Semen (Science-based technologies, 2025)
This article presents a comprehensive study of the technical and regulatory standards of the international organizations ICAO and EUROCAE in the context of modernization of aviation telecommunications equipment in Ukraine through the implementation of the ATN/IPS converged aviation telecommunications network architecture. The expediency of replacing outdated TDM networks with modern IP technologies, in particular, in terms of organizing voice communication for air traffic control based on VoIP technology, is substantiated. The requirements for the use of protocols at the key layers of the OSI model are analyzed: IPv6, TCP/UDP, IPsec, IKE2, SIP, RTP and recommendations for the quality of service. The rationale for choosing network equipment parameters in terms of minimizing packet transmission delays over IP networks in order to ensure compliance with the regulatory indicators required for the stable operation of air traffic control systems is provided. The permissible levels of jitter, packet loss, as well as the limit values of MOS and delays of payload and control signals are determined. The total delay of voice traffic transmission is calculated, taking into account encryption, buffering and the use of audio codecs in terms of ensuring the required voice quality based on the E-model. A mathematical approach is proposed to calculate the forecasting of the load on the telecommunication network of aviation telecommunications in Ukraine, based on the analysis of passenger flows between regional airports of Ukraine using a discrete Markov system. The results obtained will help to increase the efficiency of the implementation of IP technologies in aviation networks and the implementation of their modernization programs after the end of the war and the opening of Ukrainian airspace.